Enhancing college laundry management system through web-based queueing technique / Nor Azida Mohamed Noh … [et al.] - Mohamed Noh, Nor Azida; Ghazali, Muhammad Khaldun; Mohd Yassin, Anita; Ismail, Ismassabah (Faculty of Computer and Mathematical Sciences, 2023)
Students usually have little time for personal chores, such as laundry management. Doing laundry is exhausting, taking a lot of time and effort. In addition, the laundry machine always gets occupied, mainly during the middle of weekdays and weekends. Thus, this project addresses challenges in college laundry environments, including prolonged delays, uncertain machine availability, remote monitoring, and inaccessible machine locations. The objective is to design and implement a web-based Laundry Management System (LMS) with a queueing technique, explicitly employing a circular queue approach. The project follows the waterfall model, encompassing requirement analysis, design, development, and testing phases. The system has been successfully developed and has passed all functional tests. From the test data provided, the system effectively records user entries into the queue, tracks departures from the queue, indicates completion of processes and delivers notifications upon laundry process completion. As a result, the LMS efficiently addresses delays, provides real-time updates on laundry machine availability, and communicates laundry completion status through its queueing mechanism. Hence, this system proves advantageous for students in effectively managing their laundry tasks. However, several areas for enhancement exist, including the potential for mobile integration.